Discourse as a System of Filters - Zadvornaja, Jelena (Respectus Philologicus, 2003)
The article is concerned with possible ways of the discourse analysis that result from the understanding of the discourse as a system of filters limiting the production of certain utterances in a specific type of discourse. The components of the utterance, namely the propositional content, modal and illocutionary characteristics of the utterance, that can react to the discourse filtration, are singled out and considered. It is shown that in different types of discourse we may observe different nature of filtration and different degrees of deliberateness of this filtration by subjects of discourse activity. Furthermore, the problem of the typology of discourses that is based on a filtering capability of the discourse is discussed, scientific and political discourses are compared and it is shown that the scientific discourse constitutes a more rigid system of illocutionary and modal filters than the political discourse does.